Robust control-based linear bilateral teleoperation system without force sensor - Amini, H.; Dabbagh, V.; Rezaei, S.M.; Zareinejad, M.; Mardi, N.A.; Sarhan, A.A.D. (Springer Verlag (Germany), 2015)
Among the prevalent methods in linear bilateral teleoperation systems with communication channel time delays is to employ position and velocity signals in the control scheme. Utilizing force signals in such controllers significantly improves performance and reduces tracking error. However, measuring force signals in such cases, is one of the major difficulties. In this paper, a control scheme with human and environment force signals for linear bilateral teleoperation is proposed. In order to eliminate the measurement of forces in the control scheme, a force estimation approach based on disturbance observers is applied. The proposed approach guarantees asymptotic estimation of constant forces, and estimation error would only be bounded for time-varying external forces. To cope with the variations in human and environment force, sliding mode control is implemented. The stability and transparency condition in the teleoperation system with the designed control scheme is derived from the absolute stability concept. The intended control scheme guarantees the stability of the teleoperation system in the presence of time-varying human and environment forces. Experimental results indicate that the proposed control scheme improves position tracking in free motion and in contact with the environment. The force estimation approach also appropriately estimates human and environment forces.